PERGESERAN MAKNA BENTUK SAJIAN TARIAN DOLALAK MLARANAN PERIODE 1980 – 2015 - Lauditta Budiman; Sri Suwartiningsih; Esther Krisnawati (Cakrawala Jurnal Penelitian Sosial, 2019)
ABSTRACT This research set out from the phenomenon of Dance Dolalak version Mlaranan, which has experienced shifts meaning in progress. Dolalak dance appeared in the 1915 and has experienced shifts from a period in 1980-2015. The purpose of this study to explain the shift in meaning and function of the Performance Dance Version Dolalak Mlaranan period 1980-2015 which will be analyzed in semiotic Roland Barthes. Semiotics Roland Barthes; in Roland Barthes semiotic meaning of denotation and connotation plays a very important compared to its role in the science of linguistics. Direct connotations, and can be referred to as a picture of a landmark. While the connotative meaning is implied meanings. Connotative meaning of some of the signs will be a kind of myth or user myths (which emphasizes these meanings. The research method in this study is a qualitative method, and data collection is done by observation, in-depth interviews. The data were analyzed descriptively. The results showed that the shift in the meaning of dance Dolalak is the shift of the construction of meaning given guardian of culture to Dolalak, community towards Dolalak, and Founder of the Group Dolalak against Dolalak version Mlaranan, and their cultural construction, resulting in a shift in the meaning of dance Dolalak version Mlaranan in the period 1980-2015.